Social Performance pada Perbankan Syariah Indonesia: Sharia Enterprise Theory Perspective - Anggraeni, Windi Ariesti (Jurnal Wacana Ekonomi, 2019)
This study aims to analyze the disclosure of social performance or corporate social responsibility in Islamic banking using the Sharia Enterprise Theory concept approach. The method used in this research is descriptive analysis method. The data collection technique uses library research and documentation research. While the data processing technique was performed using qualitative data analysis with Miles and Huberman's model. The results of this study indicate that the level of disclosure of Corporate Social Responsibility (CSR) based on Sharia Enterprise Theory (SET) at PT. Bank Muamalat Tbk (Bank Muamalat Indonesia) during the 2011-2015 period received a very good predicate.